Comparing the Potentiality of Propane, Propanol and Octane Fuel Using in SI Engine Based on Energy-Exergy Analysis - Mizan, Md Mizanuzzaman (MIST International Journal of Science and Technology, 2021)
From the beginning of IC engine era, it is trying to improve the performance and efficiency of internal combustion engine. In this study, numerically analysis on combustion of Propane, Propanol and Octane in SI engine have been done thoroughly and presented to assess the potentiality and highlighted the comparison. For this analysis thermodynamic engine cycle model is developed for numerical analysis. Mathematical models considering fundamental equation and empirical relation are implemented in a single cylinder 4 stroke spark ignition engine (system) with the help of FORTRAN 95 to find out heat losses, friction losses, output parameter etc. Single cylinder four-stroke spark-ignition (SI) engine is considered as system. In this study, different working parameters like 8 and 12 compression ratios with three different rpm 2000, 4000 & 6000 are considered for simulation. This study shows the different comparisons of energy-exergy content (%), as example of exhaust gas 35.08 & 17.82, 37.02 & 19.22, 37.79 & 19.79 for Octane (at compression ratio 8 and 2000, 4000, 6000 rpm) etc., which explains the potentiality content and the potentiality losses in different process like combustion, mixing of gases etc. It also shows for the fuel propane and propanol in similar way with changing different operating conditions. Maximum inside cylinder temperature, 1st law and 2nd law efficiencies were determined for the fuels with respect to different compression ratio and engine speed. MIJST, Vol. 9(1), June 2020: 45-53